MoP@C Supported on Absorbent Cotton as a Highly Efficient Catalyst towards Hydrodechlorination Reaction. Issue 19 (15th September 2020) - Zhang, Lu; Yuan, Guojun; Bai, Jianliang; Ren, Lili
Abstract : This paper reports a method for preparing MoP@C synthesized from absorbent cotton. While the influence of the amount of absorbent cotton on its composition and morphology are also explored. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed that MoP@C and unmodified MoP exhibit completely different microscopic morphologies. With the gradual increase in the quality of absorbent cotton, the morphology of catalysts changed from large‐area stacking to hollow rod structure. This hollow structure effectively increases the specific surface area of the catalyst, thus providing more active sites for hydrodechlorination reaction of trichloroethylene, which exhibits relatively excellent catalytic performance in it. The catalytic activity test shows that highest activity value can reach up to 47.18 %, which was twice that of the unmodified MoP. Abstract :